Band gap engineering of graphene through quantum confinement and edge distortions - Stashans, A. (2016)
Based on the density functional theory approach we explore the chances endured by energy gap (EG) of semiconducting (armchair) graphene nanoribbons (AGNRs) when Stone-Wales (SW) defects are placed inside their lattices. Our results show that the AGNRs, which belong to the (Formula presented.) family experience an increase in their EG value. On the other hand, those belonging to 3m and (Formula presented.) families experience decrease in their EG. The maximum observed EG for pristine and distorted ribbons were (Formula presented.)2.6 and (Formula presented.)1.6 eV, respectively. Our results can be useful to understand the semiconducting properties of wider graphene nanoribbons which are already available experimentally.